PENGARUH MODEL LATIHAN MENEMBAK TERHADAP KEMAMPUAN JUMP SHOOT SISWA EKSTRAKURIKULER BOLABASKET SMA NEGERI 1 TUMPANG KABUPATEN MALANG - Imannuel Samyo Raharjo; Slamet Raharjo; Sapto Adi (Jurnal Sport Science, 2016)
ABSTRACT:Shooting is a way to put the ball into the basket in order to score points in various ways, one of which is a jump shoot. In supporting the success of the jump shoot conducted exercises with specific aspects such as the type of training that emphasizes the aspects of shooting crack of hand.The purpose of this study was to determine the effect of shooting practice models to increase the ability of the jump shoot the basketball sport.This research is a pre-experimental study with random sampling. Subjects were students in extracurricular member Tumpang active basketball SMAN 1 of 20 people with the method of random sampling of 30 students. The retrieval of data using a pretest and posttest test methods BEEF with 10 attempts jump shoot. Furthermore, the data were analyzed using SPSS 22.0 series.Based on the observations obtained t test, probability (p) exercises follow through = 0.000 <0.05. From these results indicate p <0.05, which means that H0 is rejected. So we can conclude shooting practice models affect the ability of students' extracurricular shoot jump SMAN 1 Tumpang. Suggestions for further research by considering the different variables or coupled to the control variables with the subject of more extensive research.Keywords: extracurricular basketball, exercise whip hand, jump shoot